CATEGORIAL ANALYSIS MODEL: THE INTERACTIVE LEARNING OBJECTS OF EDUCATION 4.0 - Moreno Jiménez, Sonia
A categorical analysis model is proposed, which allows to formally study the characterization of objects, media, spaces and resources in general, involved in the conceptual and contextual framework of education 4.0. The starting point consisted of modeling the problem where attributes, variables, and categorical implications of Learning Objects were defined: Virtual, Physical, Mixed Technological, and the notion of interactivity and interactions involved, which was developed in three phases. First, revision of the epistemological and categorical notion, Second, problematization around the notion of virtuality and its origin; and third, it addressed the concept of interaction in relation to interactivity and the typology involved in the current technological and techno-educational framework. This research study assumed theoretical analyzes that allowed the formal definition of the Interactive Learning Object -OIA-, its levels and degrees of interactivity as didactic means in the structure of educational knowledge 4.0.